Edukasi Seksual Melalui Buklet (Es Labu) dalam Meningkatkan Pengetahuan dan Sikap Pengasuh Anak Prasekolah - Sholihah, Wardatus; Rukmini, Rukmini; Syaiful, Yuanita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of sexual education using booklets on the knowledge and attitudes of caregivers of preschool children. The method used is a quasi-experimental pre-test and post-test design involving 50 caregivers of preschool children. The results of the study showed that after being given an intervention on sexual education through booklets to caregivers who have preschool children, there was an increase in caregiver knowledge with a value (P <0.001) and an increase in caregiver attitudes with a value (P <0.001). In conclusion, providing sexual education through booklets to caregivers of preschool children has proven effective in increasing caregiver knowledge and attitudes so that it can prevent sexual crimes against children. Keywords: Preschool Children, Booklet Education, Sexual Violence, Caregivers